2022
DOI: 10.1039/d2cy00426g
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of triazines from alcohols and amidines using supported Pt nanoparticle catalysts via the acceptorless dehydrogenative methodology

Abstract: We report a cost-effective, green, and acceptorless dehydrogenative one-pot synthesis of triazine from primary alcohols and amidines using alumina-supported Pt nanoparticle catalyst (Pt/Al2O3). This reaction proceeds with high atom efficiency...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Poly and colleagues synthesised triazines (122) using aliphatic/aromatic amidines (120) and aliphatic/benzylic primary alcohols (121) catalysed by recyclable (six times) alumina-supported PtNPs (Pt/Al 2 O 3 ) through cyclocondensation and acceptor-less sequential dehydrogenation (Scheme 34). 87 The catalysts were prepared from alumina and Pt(NH 3 ) 2 (NO 3 ) 2 and were characterised by DF-STEM, DF-STEM-EDS, DF-STEM-EELS mapping, etc.…”
Section: Ptnpsmentioning
confidence: 99%
“…Poly and colleagues synthesised triazines (122) using aliphatic/aromatic amidines (120) and aliphatic/benzylic primary alcohols (121) catalysed by recyclable (six times) alumina-supported PtNPs (Pt/Al 2 O 3 ) through cyclocondensation and acceptor-less sequential dehydrogenation (Scheme 34). 87 The catalysts were prepared from alumina and Pt(NH 3 ) 2 (NO 3 ) 2 and were characterised by DF-STEM, DF-STEM-EDS, DF-STEM-EELS mapping, etc.…”
Section: Ptnpsmentioning
confidence: 99%
“…At the end of the reaction, the desired products were obtained in moderate to good yields up to 91%. In another example, Poly et al demonstrated the use of primary alcohols and amidines as molecular building blocks for triazine synthesis by applying alumina-supported Pt (Pt/Al 2 O 3 ) nanoparticle catalyst ( Scheme 12 b) [ 126 ]. The acceptorless dehydrogenative coupling reaction was carried out in one pot with high atom economy and good yields of up to 93%.…”
Section: Six-membered Ringsmentioning
confidence: 99%
“…[21] The known methods for the preparation of guanamines are diverse as can be illustrated by synthetic approaches to 6phenyl-1,3,5-triazine-2,4-diamine (6 e), which is also known as benzoguanamine (Scheme 1). These approaches include the Suzuki coupling of 6-chloro-1,3,5-triazine-2,4-diamine (7) with phenylboronic acid (8), [22] ring rearrangement of 5-phenyl-1,2,4triazine (9) upon the treatment with potassium amide (10), [23] the reaction of guanidine (11) and benzyl alcohol (12) under the alumina-supported Pt catalysis, [24] the cyclocondensation of N-cyanobenzamidine (13) and guanidine (11), [25] and the reaction of N-benzoylcyanoguanidine (14) with cyanamide (15). [26] However, the most practical methods with the greatest atom economy [27] utilize the base-catalyzed reaction of cyanoguanidine (16) with benzonitrile (17 e) for the synthesis of benzoguanamine (6 e).…”
Section: Introductionmentioning
confidence: 99%